2011
DOI: 10.1111/j.1399-3054.2011.01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and calcium receptor CAS promote Arabidopsis thaliana de‐etiolation

Abstract: As a second messenger, the free cytosolic calcium ion (Ca(2+)) plays important roles in many biochemical and physiological processes including photosynthesis in plants. In this study, we investigated morphological changes, chlorophyll accumulation and chloroplast development during early photomorphogenesis in etiolated seedlings of both Arabidopsis thaliana wild type (WT) and those with the antisense of CAS, a calcium sensor (CASas). Seedlings were grown at high, medium and low Ca(2+) concentrations to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Our previous study also reported that Ca addition dramatically alleviated the negative effects of AR on seed germination, seedling growth and photosynthesis [3]. Free Ca ion within cell is a second messenger for conveying internal and external signals by Ca sensors that subsequently regulate diverse cellular processes in plants [17]. Calmodulin (CaM) and calcium-dependent protein kinase (CDPK), two major types of Ca sensor, play important roles in Ca signaling and further response to diverse stresses in plants [51].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our previous study also reported that Ca addition dramatically alleviated the negative effects of AR on seed germination, seedling growth and photosynthesis [3]. Free Ca ion within cell is a second messenger for conveying internal and external signals by Ca sensors that subsequently regulate diverse cellular processes in plants [17]. Calmodulin (CaM) and calcium-dependent protein kinase (CDPK), two major types of Ca sensor, play important roles in Ca signaling and further response to diverse stresses in plants [51].…”
Section: Discussionmentioning
confidence: 86%
“…Chlorophyll was extracted from approximately 0.1 g fresh leaf slices directly into 10 ml ice-cold acetone (80%, v/v). The chlorophyll content (mg g −1 fresh weight (FW)) was determined as described previously [17].…”
Section: Methodsmentioning
confidence: 99%
“…At least three seedlings and more than 40 chloroplasts for each time point were analyzed (Huang et al, 2012). The samples were then washed with phosphate buffer solution (0.1 M, pH 7.0), and post-fixed for 4 h with 1% OsO 4 at room temperature.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…The total Chl content (mg g -1 fresh weight [FW]) in barley seedlings at each time point of illumination was measured according to Huang et al (2012). Absorption of the extract was measured at 663 and 645 nm with a spectrometer (Cary 50 UV-VIS, Varian, Mulgrave, Australia).…”
Section: Chlorophyll Content Net Photosynthetic Rate and Chlorophylmentioning
confidence: 99%
See 1 more Smart Citation